Shift & reset strategies for addressing serious issues in a connected society - Reich, Brian, 1977- (Wiley, 2011)
"Essential strategies the nonprofit community can use to take advantage of rapidly changing technologies and new communication methods in our ultra-connected societyIn these challenging economic times, it is more important than ever for nonprofits to focus on shaping policy, building capacity, developing talent, improving their marketing and promotion, fundraising, and developing partnerships/collaboration for organizational success. Shift & Reset: Strategies for Supporting Causes in a Connected Society teaches the nonprofit/social change/philanthropy/cause community how to take advantage of rapidly changing technologies and new communication ecosystem that exist in our connected society. Addresses the most critical challenges facing the nonprofit/social change/philanthropy/cause community Re-envisions how we support causes and address serious issues in our connected society Outlines how organizations must operate?and what happens when they don't re-think their work Features interviews with over twenty-five leading thinkers/authors/organizational leaders Innovative and right on time, Shift & Reset equips nonprofit professionals with a set of three core principles, a five-step checklist of immediate action items, as well as a list of ten "must-read" items"--